Toward optimization of centrifugal barrel polishing procedure for treatment of niobium cavities - Prudnikava, A; Tamashevich, Y; Steirle, A; Yanushkevich, K; Foster, B (Institute of Electrical and Electronics Engineers, 2018)
Centrifugal barrel polishing (CBP) is a simple and environmentally friendly method that can be applied for mechanical abrasion of the cavity interior in order to remove the mechanically damaged surface after its production. The CBP recipes described in the literature, however, require CBP to be performed in many stages, require long processing times and nevertheless are unable to provide good cavity RF performance without additional chemical processing. Here, we report new results on characterization of cavity surfaces treated with a typical CBP recipe, including the contamination with abrasive particles, plastic deformation and hydrogen contamination, and critically evaluate it. Methods to reduce the depth of significant plastic deformation as well as the modified commercially viable CBP procedure followed by final electropolishing are proposed and tested on samples.